But the denominator is so large

Calculus Level 4

n = 0 ( 1 ) n 3 n + 1 ( 2 n + 1 ) = ? \large \sum\limits_{n=0}^\infty \frac{(-1)^n}{3^{n+1}(2n+1)} = \ ?

These problem is from a test by Professor Maria do Ceú.
π π π 2 \frac{π}{2} 3 6 \frac{\sqrt{3}}{6} π 2 6 \frac{π\sqrt{2}}{6} π 3 18 \frac{π \sqrt{3}}{18} π 3 9 \frac{π\sqrt{3}}{9} 3 3 \frac{\sqrt{3}}{3}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

We know that n = 0 ( 1 ) n x 2 n + 1 2 n + 1 = arctan ( x ) , x ] 1 , 1 [ \sum\limits_{n=0}^\infty (-1)^n \frac{x^{2n+1}}{2n+1} = \arctan(x) , \forall x\in]-1,1[ . Therefore, n = 0 ( 1 ) n x 2 n + 2 2 n + 1 = x arctan ( x ) , x ] 1 , 1 [ \sum\limits_{n=0}^\infty (-1)^n \frac{x^{2n+2}}{2n+1} = x\arctan(x) , \forall x\in]-1,1[ . It is clear that n = 0 ( 1 ) n 1 3 n + 1 ( 2 n + 1 ) = n = 0 ( 1 ) n 1 3 n + 1 ( 2 n + 1 ) = n = 0 ( 1 ) n ( 1 3 ) n + 1 ( 2 n + 1 ) = \sum\limits_{n=0}^\infty (-1)^n \frac{1}{3^{n+1}(2n+1)}=\sum\limits_{n=0}^\infty (-1)^n \frac{\frac{1}{3^{n+1}}}{(2n+1)}=\sum\limits_{n=0}^\infty (-1)^n \frac{{\left( \frac{1}{3} \right)}^{n+1}}{(2n+1)}= n = 0 ( 1 ) n ( 1 3 ) 2 ( n + 1 ) ( 2 n + 1 ) = n = 0 ( 1 ) n ( 1 3 ) 2 n + 2 ( 2 n + 1 ) \sum\limits_{n=0}^\infty (-1)^n \frac{{\left( \frac{1}{\sqrt{3}} \right)}^{2(n+1)}}{(2n+1)}=\sum\limits_{n=0}^\infty (-1)^n \frac{{\left( \frac{1}{\sqrt{3}} \right)}^{2n+2}}{(2n+1)} and, because 1 3 ] 1 , 1 [ \frac{1}{\sqrt{3}} \in ]-1,1[ , n = 0 ( 1 ) n ( 1 3 ) 2 n + 2 ( 2 n + 1 ) = 1 3 arctan ( 1 3 ) \sum\limits_{n=0}^\infty (-1)^n \frac{{\left( \frac{1}{\sqrt{3}} \right)}^{2n+2}}{(2n+1)} =\frac{1}{\sqrt{3}}\arctan\left(\frac{1}{\sqrt{3}}\right) . So, we have that n = 0 ( 1 ) n 1 3 n + 1 ( 2 n + 1 ) = 1 3 arctan ( 1 3 ) = π 3 18 \sum\limits_{n=0}^\infty (-1)^n \frac{1}{3^{n+1}(2n+1)}=\frac{1}{\sqrt{3}}\arctan\left(\frac{1}{\sqrt{3}}\right)=\frac{π\sqrt{3}}{18} .

did the same way

Shashank Rustagi - 5 years, 12 months ago
Chew-Seong Cheong
Dec 13, 2017

Relevant wiki: Maclaurin Series

Consider the Maclaurin series for tan 1 x \tan^{-1} x :

n = 0 ( 1 ) n x 2 n + 1 2 n + 1 = tan 1 x Multiplying both sides by x n = 0 ( 1 ) n ( x 2 ) n + 1 2 n + 1 = x tan 1 x Putting x = 1 3 n = 0 ( 1 ) n 3 n + 1 ( 2 n + 1 ) = 1 3 tan 1 1 3 = 1 3 × π 6 = π 3 18 \begin{aligned} \sum_{n=0}^\infty \frac {(-1)^n x^{2n+1}}{2n+1} & = \tan^{-1} x & \small \color{#3D99F6} \text{Multiplying both sides by }x \\ \sum_{n=0}^\infty \frac {(-1)^n\left(x^2\right)^{n+1}}{2n+1} & = x \tan^{-1} x & \small \color{#3D99F6} \text{Putting }x= \frac 1{\sqrt 3} \\ \sum_{n=0}^\infty \frac {(-1)^n}{3^{n+1}(2n+1)} & = \frac 1{\sqrt 3} \tan^{-1} \frac 1{\sqrt 3} \\ & = \frac 1{\sqrt 3} \times \frac \pi 6 \\ & = \boxed{\dfrac {\pi \sqrt 3}{18}} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...